Practice-Centered Approach to Design Cooperative Healthcare Information Systems: Data, Architectural and Organizational Challenges - Marref, Rahma; Abou Amsha, Khuloud; Lewkowicz, Myriam (Computing and Informatics, 2022)
The healthcare sector is a collaborative environment that requires a joint action for delivering care. Health professionals who work in different organizations or settings must assimilate a massive amount of data generated during the patient care journey. Electronic healthcare records offer a starting point for supporting cooperation among healthcare professionals by saving and sharing traces of the patient's medical acts. However, we claim that these records merely store and share data, which disregards how health professionals use this data to understand the patients' situations and make decisions. We argue that focusing on the cooperative practices of managing patients gives designers new insights to design future healthcare information systems supporting cooperation, and we identify challenges related to this design approach.